PELAKSANAAN SUPERVISI AKADEMIK OLEH KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU DI MADRASAH TSANAWIYAH NEGERI 5 KOTA JAMBI - Dasryannisa, Natijahurrohmah; MY, Mahmud; Purnama, Boby Yasman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the implementation of academic supervision by the head of madrasah in improving teacher performance at MTsN 05 Jambi City and to identify the obstacles encountered in its implementation. This research employed a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that academic supervision was carried out through three stages: planning, implementation, and follow-up. The planning stage involved preparing supervision programs and schedules. The implementation stage was conducted through the examination of learning administration and classroom observations. Furthermore, the follow-up stage was carried out by providing feedback, guidance, motivation, and reinforcement to teachers. The implementation of academic supervision had a positive impact on teacher performance, particularly in improving teaching competence, work motivation, and the utilization of technology in the learning process. The obstacles identified included scheduling conflicts due to unexpected official duties and limitations in educational facilities and infrastructure. Based on the findings, it can be concluded that the implementation of academic supervision by the head of madrasah at MTsN 05 Jambi City has been carried out effectively and has contributed to improving teacher performance.